Analisis Dampak Usaha Pembuatan Genteng Terhadap Kondisi Lingkungan dan Sosial Ekonomi Masyarakat Desa Ngembalrejo - Putri Suryaningsih; Millatul Lailiyah; Febrina Nur Hikmah; Miftahul Fadhlilah; Muhammad Rafiqul Usman (FKIP, Universitas Palangka Raya, 2024)
This research was conducted behind the environmental and health conditions of the ngembalrejo community which were disrupted due to the tile making industry with a location close to the residents. The tile making is located at the location of Ngembalrejo village, Bae District, Kudus Regency. So that the Ngembalrejo area is indeed famous as a tile making industry area. With raw materials that cannot be renewed to materials for burning, tile making finally comes a variety of impacts that affect the community around the Ngembalrejo village area. The emergence of this impact is caused by the factor of sugarcane burning materials and plastic waste from PT. Temple, so that it can create risks and impacts on the environment and public health. So in writing this article aims to analyze the impact that occurs due to the tile making industry in Ngembalrejo village. By using interview techniques with Mrs. Imro'atul Nasihah as a tile making industry entrepreneur as well as interviews of local residents to boarding house residents and observation or observation at the affected location to the tile manufacturing site, with this technique we collect data as much as possible.